2008
DOI: 10.1007/s11998-007-9066-4
|View full text |Cite
|
Sign up to set email alerts
|

The physical chemistry of organic coatings revisited—viewing coatings as a materials scientist

Abstract: Modern organic coatings are complex materials which must be observed and interpreted from the viewpoint of what has become known as Materials Science. Paints, as most of us first learned to name organic coatings, were originally designed and conceived as art forms. Visual artists developed their own applied colorants; part of an artist's success depended on these skills (consider Leonardo da Vinci). Today, one's skills as a materials scientist are perhaps the most crucial attributes of the true coatings scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Because the conductivity of the polymer is high, variations of the transition resistance between the electrodes and the polymer get a stronger influence on the measured current. The conductivity of S–PEG150–SS is sufficient for many kinds of applications such as antistatic coatings7, 25 or flock coatings 26. Similar to the viscosity, the conductivity is decreased as the molar mass of PEG chains in S–PEG x –SS increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the conductivity of the polymer is high, variations of the transition resistance between the electrodes and the polymer get a stronger influence on the measured current. The conductivity of S–PEG150–SS is sufficient for many kinds of applications such as antistatic coatings7, 25 or flock coatings 26. Similar to the viscosity, the conductivity is decreased as the molar mass of PEG chains in S–PEG x –SS increases.…”
Section: Resultsmentioning
confidence: 99%
“…Conductive polymers have attracted significant attention for various industrial applications such as for plating technology,1 sensors and lab‐on‐chip technology,2 battery development,3, 4 fuel cells,5, 6 as well as for antistatic and anticorrosive coatings 7. A common approach to obtain electrical conductive polymers is the incorporation of dispersible conductive additives into the polymer network 8.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions growing mitosporic fungi are detected on metals, and the variety of them determines the corrosion behaviour (Yang et al 1996). To protect metals from damage caused by microorganisms, polymeric films have been investigated (Bierwagen 2008;Binkauskienė et al 2009). Recently much attention has been devoted to studies of zinc-polymeric coatings, which are widely used in automotive industry and to protect railway transport, large-block buildings, bridges and other objects made of steel to protect them from corrosion and mechanical damages (Kikuchi, Streekumari 2002;Marchebois et al 2002;Tü ken 2006).…”
Section: Influence Of Mitosporic Fungi Upon Zinc-polymeric Coatings Omentioning
confidence: 99%
“…Bierwagen concluded that the total system performance of the Mg-rich primer + topcoat was a synergistic blend of the cathodic/sacrificial protection of the primer, the inhibition/thin barrier layer effects of the MgO/Mg(OH) 2 formed as oxidation products of the Mg, the barrier properties of the polymer in the Mg-rich primer, plus the barrier properties of the topcoat [56]. Indeed, panels coated with Mg-rich primers have performed very well on outdoor exposure at various sites across the US.…”
Section: Unnoticed Factors That Influence the Behavior Of Mg-rich Primentioning
confidence: 99%